The impact of educational attainment on diagnostic and treatment delays in multiple sclerosis: a nationwide cohort study in Denmark - Elisabeth Framke; Melinda Magyari (Therapeutic Advances in Neurological Disorders)
Background: In multiple sclerosis (MS), the educational gradient in diagnostic and disease-modifying treatment (DMT) delays is sparsely examined, and the results are mixed. Objectives: Among patients with relapsing-remitting MS (RRMS), we aimed to examine the educational gradient in diagnostic delay and delay in the initiation of the first DMT. Design: A nationwide cohort study. Methods: We linked the Danish Multiple Sclerosis Registry with other nationwide registries. Diagnostic delay was evaluated in 4344 patients ⩾20 years at clinical onset with clinical onset from January 1, 2012, onwards, diagnosed by March 1, 2023. DMT delay was evaluated in 5402 patients ⩾20 years at MS diagnosis who were diagnosed from January 1, 2012, to March 1, 2022, with DMT initiation follow-up until March 1, 2023. The highest completed education before onset and diagnosis, respectively, was categorized using the International Standard Classification of Education (ISCED) into low (ISCED 0–2), medium (ISCED 3–4) and high (ISCED ⩾5) education. Endpoints were categorized according to their duration into four groups based on a population-specific quartile split. The highest quartile comprised long duration (⩾500 days (diagnostic delay) and ⩾76 days (DMT delay)). We calculated crude and adjusted odds ratios (OR) with 95% confidence intervals (CI). Results: The mean age was 36.7 years (SD = 10.3, diagnostic delay population) and 39.2 years (SD = 10.9, DMT delay population). Most were female (67.4% and 68.3%) and of Danish origin (90.3% and 90.5%). Patients with low educational attainment did not have higher odds of diagnostic delay (OR = 1.05; 95% CI: 0.81–1.35) but had higher odds of DMT delay (OR = 1.48; 95% CI: 1.17–1.87) compared to patients with high educational attainment. Conclusion: In adult patients with RRMS, low educational attainment was associated with higher odds of DMT delay but not diagnostic delay. Targeted interventions are needed to address educational disparities in healthcare access and treatment initiation.